2012
DOI: 10.1107/s1744309112016843
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary crystallographic studies of CCM3 in complex with the C-terminal domain of MST4

Abstract: MST4 is a member of the GCKIII kinases. The interaction between cerebral cavernous malformation 3 (CCM3) and GCKIII kinases plays a critical role in cardiovascular development and in cerebral cavernous malformations. The complex of CCM3 and the C-terminal domain of MST4 has been constructed, purified and crystallized, and a diffraction data set has been collected to 2.4 Å resolution. The crystal of the CCM3-MST4 C-terminal domain complex belonged to space group P4 1 2 1 2 or P4 3 2 1 2, with unit-cell paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The CCM3/PDCD10 N-terminal α-helical region of approximately 70 residues [24,25] does indeed heterodimerize with the regulatory domains of all three GCKIIIs [23,[26][27][28][29][30]. Furthermore, a recent study showed that essentially full-length CCM3/PDCD10 cocrystallizes with the C-terminus (residues 346-416) of MST4 [31], and even more recently the crystallographic structure of the heterodimer between CCM3/PDCD10 (residues 9-212) and the C-terminus of MST4 (residues 325-413) has been reported [30]. In this complex, MST4 (325-413) assumes a conformation containing three α-helices that interact with the α-helices 1-4 of CCM3/PDCD10 [30].…”
Section: Figure 2 Modelling Of Human Gckiii Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCM3/PDCD10 N-terminal α-helical region of approximately 70 residues [24,25] does indeed heterodimerize with the regulatory domains of all three GCKIIIs [23,[26][27][28][29][30]. Furthermore, a recent study showed that essentially full-length CCM3/PDCD10 cocrystallizes with the C-terminus (residues 346-416) of MST4 [31], and even more recently the crystallographic structure of the heterodimer between CCM3/PDCD10 (residues 9-212) and the C-terminus of MST4 (residues 325-413) has been reported [30]. In this complex, MST4 (325-413) assumes a conformation containing three α-helices that interact with the α-helices 1-4 of CCM3/PDCD10 [30].…”
Section: Figure 2 Modelling Of Human Gckiii Structuresmentioning
confidence: 99%
“…The interactions between CCM3/PDCD10 and GCKIIIs [23,26,28,29], and between CCM3/PDCD10 and paxillin [69], suggests that GCKIIIs could be recruited directly to focal adhesions, although (to our knowledge) this has not been demonstrated experimentally. Overexpression of MST3 (431) inhibits cell migration and invasion and is associated with an increase in the phosphorylation at Tyr 31 and Tyr 118 of paxillin [35]. In contrast, depletion of MST3 or overexpression of dominant-negative MST3 (431) (T178A) enhances cell migration and reduces tyrosine residue phosphorylation of paxillin.…”
Section: Gckiiis and Paxillinmentioning
confidence: 99%
“…The CCM proteins can be found in a dynamic trimeric complex, with CCM2, a scaffolding protein, acting as the hub and interacting directly with CCM1 and CCM3; however, each also interacts with a variety of other signaling, cytoskeletal, and adaptor proteins [60, 87, 88] (Figure 1C). Several additional direct interactors for each of the CCM proteins have been identified, including, for CCM1, the small GTPase RAP1, the membrane anchor protein heart of glass 1 (HEG1) [89], and the integrin cytoplasmic domain associated protein-1 (ICAP1) [90, 91]; for CCM2, MAPK/ERK kinase kinase-3 (MEKK3) (leading to p38 activation) [92, 93]; and for CCM3, the three Germinal Center Kinase III (GCKIII) serine/threonine (STE20) kinases STK24 and STK25 (via which CCM3 interacts with moesin), and MST4, as well as the scaffolding proteins paxillin and striatin (Figure 1C) [94-100]. Of all these bona fide interactors, MEKK3 [92, 93, 101-104], has emerged as a key player in the formation and progression of CCM lesions.…”
Section: Hereditary Hemorrhagic Cerebrovascular Diseasementioning
confidence: 99%
“…5O,P). Golgi morphology and deployment, in part regulated by the CCM3 interactor STK25 (Matsuki et al, 2010;Ceccarelli et al, 2011;Xu et al, 2012), were normal (not shown).…”
Section: Ccm3 Affects Neuronal Morphology In Vivo and In Vitromentioning
confidence: 99%